2019
DOI: 10.1007/s00018-019-03403-y
|View full text |Cite
|
Sign up to set email alerts
|

PIWI family proteins as prognostic markers in cancer: a systematic review and meta-analysis

Abstract: Background: PIWI proteins, which interact with piRNAs, are implicated in stem cell and germ cell regulation, but have been detected in various cancers, as well.Objectives: In this systematic review, we explored, for the first time in the literature (to our knowledge), the association between prognosis in patients with cancer and intratumoral expression of PIWI proteins.Data sources: PubMed, Embase and Web of Knowledge databases were searched for the relevant cohort studies. Study eligibility criteria:Prospecti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 127 publications
0
6
0
Order By: Relevance
“…Recently, PIWI family proteins have been considered as prognostic markers for various malignancies. A systematic review and meta-analysis showed that PIWI family proteins have the potential to indicate the prognosis of various cancer, and lower PIWIL4 expression levels indicate worse prognosis in cancer [ 46 ]. Iliev et al demonstrated that decreased expression levels of PIWIL4 indicated worse long-term survival in patients with renal cell carcinoma [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, PIWI family proteins have been considered as prognostic markers for various malignancies. A systematic review and meta-analysis showed that PIWI family proteins have the potential to indicate the prognosis of various cancer, and lower PIWIL4 expression levels indicate worse prognosis in cancer [ 46 ]. Iliev et al demonstrated that decreased expression levels of PIWIL4 indicated worse long-term survival in patients with renal cell carcinoma [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Identified as nuclear proteins, there are four human Piwis: PiwiL1, PiwiL2, PiwiL3 and PiwiL4 (39). These proteins form the piRISC complex with piRNA to regulate germline transposable elements and the protein-coding gene transposable elements in soma (13,40).…”
Section: Discussionmentioning
confidence: 99%
“…So far, four PIWI family proteins have been identified in humans: PIWIL1 (HIWI), PIWIL2 (HILI), PIWIL3, and PIWIL4 (HIWI2). Among the PIWI family, the most studied cancers were colorectal cancer and breast cancer, and PIWIL1 is the most studied protein among the PIWI family (8).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to piwil1's expression pattern in normal tissues, testicular cancer had the largest proportion of samples with high piwil1 expression. Most cancer types displayed very low piwil1 expression (i.e., very few samples with an expression of >5 FPKM) (8). PIWIL1 rs10773771 C>T is associated with a risk of large artery atherosclerosis stroke (10).…”
Section: Introductionmentioning
confidence: 99%